PENGARUH PERBEDAAN INDIVIDU DALAM PERILAKU KERJA - Abu Hanifah; Sumiati (PT. Hasba Edukasi Mandiri, 2025)
Each individual has its own uniqueness, this individual uniqueness is what is then called individual differences. Understanding individual differences is very important for a leader or manager, because these individual differences will later affect work behavior. By knowing the differences of each individual in an organization, it is hoped that it can lead the organization in a better direction. Therefore, the writing of this work aims to examine the differences in individual and work behavior and how they are related between individual differences and work behavior. This paper is written using the library research method where the author conducts a study of books and other references related to the material Individual differences and work behavior. From this study, the author found several things, namely that there are several things that underlie the occurrence of individual differences, both internal factors and external factors covered in the primary dimension and secondary dimension. These differences will later become characteristics for an individual that can affect an individual's work behavior.